2015
DOI: 10.1007/s10815-015-0615-y
|View full text |Cite
|
Sign up to set email alerts
|

The anti-Müllerian hormone (AMH) acts as a gatekeeper of ovarian steroidogenesis inhibiting the granulosa cell response to both FSH and LH

Abstract: These findings contribute in clarifying the relationship between hormones regulating the early phase of steroidogenesis confirming that AMH is playing a suppressive role on CYP19A1 expression stimulated by gonadotropin in hGCs. Furthermore, a similar inhibitory effect for AMH was observed on P450scc gene expression when activated by gonadotropin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 22 publications
3
47
0
2
Order By: Relevance
“…In the infantile ovary, our findings showed that AMH treatment significantly repressed FSH-mediated induction of Cyp19a1 aromatase, as previously described for human luteinized granulosa cells in vitro (Grossman et al 2008, Chang et al 2013, Prapa et al 2015, Sacchi et al 2016. This effect unlikely resulted from decreased FSHR expression as described in human tumoral granulosa cells (Pellatt et al 2011), since AMH did not alter Fshr transcript abundance, albeit we cannot exclude that it could have affected FSHR protein levels.…”
Section: :2supporting
confidence: 85%
See 2 more Smart Citations
“…In the infantile ovary, our findings showed that AMH treatment significantly repressed FSH-mediated induction of Cyp19a1 aromatase, as previously described for human luteinized granulosa cells in vitro (Grossman et al 2008, Chang et al 2013, Prapa et al 2015, Sacchi et al 2016. This effect unlikely resulted from decreased FSHR expression as described in human tumoral granulosa cells (Pellatt et al 2011), since AMH did not alter Fshr transcript abundance, albeit we cannot exclude that it could have affected FSHR protein levels.…”
Section: :2supporting
confidence: 85%
“…The present study reveals that FSH represses Amh expression specifically in the first follicular waves, wherein we previously showed that FSH induces a consistent Cyp19a1 aromatase expression without altering that of Ccnd2 (François et al 2017). Since other studies reported that AMH prevents FSH-induced E2 synthesis (Grossman et al 2008, Chang et al 2013, Prapa et al 2015, Sacchi et al 2016, possibly by down-regulating FSHR expression (Pellatt et al 2011), and that it regulates FSH-mediated follicular growth (McGee et al 1997, Durlinger et al 2001, we next sought to investigate whether the observed decrease in Amh expression could facilitate FSH-mediated Cyp19a1 expression and explain the loss of FSH-mediated Ccnd2 expression in preantral/early antral follicles. We therefore tested the effect of a treatment by AMH on the expression of Cyp19a1, Fshr and Ccnd2 in the infantile ovary.…”
Section: Amh Prevents Fsh-mediated Induction Of Cyp19a1 Aromatase Witsupporting
confidence: 57%
See 1 more Smart Citation
“…In fetal development, AMH prevents development of the Müllerian ducts during male sex differentiation . In addition, AMH plays an important role in ovarian function and folliculogenesis, modulating ovarian sensitivity to gonadotropins, and in gene expression, leading to production of ovarian steroids . Anti‐Müllerian hormone is a well‐described biomarker of ovarian reserve and has been used to predict age‐at‐menopause and primary ovarian insufficiency .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is also possible that male signaling mediated by amh ( amhy and/or amha ) suffices to override this cyp19a1a -dependent, developmentally programmed ovarian differentiation. In fact, AMH has suppressive effects on aromatase in other vertebrates (e.g., human granulosa lutein cells) [Grossman et al, 2008;Sacchi et al, 2016]. This would explain the absence of cyp19a1a expression in some XY and XX individuals with amh expression but no apoptosis.…”
mentioning
confidence: 99%